Comparison Awareness Behavior Sexual Healthy between Adolescents Who Are Dating and Who Are Not Dating: Implications for Sex Education in Schools - Cusinia, Azahra Hardi; Nurfarhanah, Nurfarhanah (International Journal of Research in Counseling and Education, 2025)
Adolescence is a critical phase in the development of sexual behavior, making appropriate sexual education essential. This study aims to compare the level of awareness regarding healthy sexual behavior between adolescents who are dating and those who are not. The research involved 127 high school students in Padang City, divided into two groups based on dating status: 55 students who were in a dating relationship and 72 students who were not. Data were collected using a 4-point Likert scale instrument consisting of 35 valid items (Cronbach’s alpha = 0.884). Due to the non-normal distribution of data, the Mann–Whitney U test was used for analysis. The results showed no significant difference between the two groups in terms of awareness of healthy sexual behavior (p > 0.05). These findings suggest that dating status is not a primary determinant of adolescents’ sexual awareness. Other factors—such as sexual education, family communication, self-control, and cultural values—may play a more influential role. The results highlight the importance of developing comprehensive, value-based sexual education programs in schools that address all adolescents, regardless of their relationship status. This study provides practical contributions for educators, counselors, and policymakers in fostering healthy sexual character development among adolescents.